RP-HPLC Method for the Determination of Tamsulosin in Bulk and Pharmaceutical Dosage Forms - Laha, T.K.; Mishra, S.; Sen, S. (Asian Journal of Chemistry, 2010)
A sensitive, selective and precise high-performance liquid chromatographic method of analysis of tamsulosin both in a bulk drug and in formulations was developed and validated. The chromatographic separation was achieved on a Microbondapak C18 (250 cm × 4.6 mm, 5 μm) column using methanol:phosphate buffer (pH 7.8) (80:20 v/v) as a mobile phase. Solution concentrations were measured on a weight basis to avoid the use of an internal standard. The detection wavelength was 230 nm. This system was found to give the sharp peak for tamsulosin (RT at 3.42 ± 0.05 min). Tamsulosin was subjected to acid and alkali hydrolysis, oxidation, dry heat, wet heat and photo degradation. The drug underwent degradation under acidic and basic conditions and upon oxidation. The degraded products were well resolved from the pure drug with significant difference in their RT values. The response of the drug was found to be linear in the range of 5-250 μg/mL (r2 > 0.999). The method was validated for the precision and recovery. The limit of detection and quantitation were 0.215 and 0.739 μg/mL, respectively. As the method could effectively separate the drug from its degradation products, it can be employed for analysis of stability samples.